Association of cumulative remnant cholesterol exposure with adverse outcomes after PCI in acute ST-segment elevation myocardial infarction - Yazhao Sun; Feilong Shao; Xinxin Xu; Yayun Liu; Ya Ma (Frontiers in Cardiovascular Medicine, 2026)
Background Remnant cholesterol (RC) has been associated with adverse cardiovascular outcomes; however, the relationship between cumulative RC exposure and clinical outcomes after percutaneous coronary intervention (PCI) in patients with ST-segment elevation myocardial infarction (STEMI) remains unclear. This study aimed to evaluate the association between cumulative remnant cholesterol (cumRC) and major adverse cardiovascular and cerebrovascular events (MACCEs) after PCI. Methods This retrospective landmark study included 632 patients with STEMI who underwent successful PCI with drug-eluting stent implantation. RC was measured at baseline and at 2 and 4 years after PCI. cumRC was calculated as the area under the RC concentration-time curve over the fixed 4-year exposure period using the trapezoidal rule. The RC measurement obtained 4 years after PCI was defined as the landmark time point, followed by a 1-year outcome assessment. Multivariable logistic regression, subgroup analyses, and sensitivity analyses were performed. Results During the 1-year post-landmark follow-up, 186 participants experienced at least one MACCE (29.4%). After multivariable adjustment, each 1 mmol/L·year increase in cumRC was associated with 36% higher odds of MACCEs (odds ratio [OR], 1.36; 95% confidence interval [CI], 1.15–1.61; P < 0.001). Compared with the lowest tertile, the second and third tertiles were associated with higher odds of MACCEs (second tertile: OR, 2.35; 95% CI, 1.47–3.76; P < 0.001; third tertile: OR, 2.71; 95% CI, 1.60–4.66; P < 0.001). No significant interactions were observed across the prespecified subgroups. The results remained consistent after separate adjustment for baseline low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C), apolipoprotein B (ApoB), or baseline RC. Conclusion Higher cumRC exposure was independently associated with higher odds of subsequent MACCEs in patients with STEMI after PCI. Prospective multicenter studies are needed to confirm this association and evaluate its clinical relevance.